Malaria Prevention Strategies and Associated Challenges among College Students in Anambra State, Nigeria - Anieche, John Emenike; Orji, Chinenye Nwatoka; Okonkwo, Oluchukwu Ginika; Chude, Jane Ifediba; Ezekiel, Rosemary; Okonkwo, Oluchukwu Ginika (British Journal of Healthcare and Medical Research, 2026)
Malaria is an endemic disease in Nigeria with high cost of treatment and economic burden with its prevention better than cure. This is a descriptive study that determined the malaria preventive strategies and associated challenges among College students in Anambra State, Nigeria. A Sample of 365 respondents was proportionately and randomly drawn from a population 4,135 College students for the study. A 29-item structured questionnaire that was tested for internal consistency with 0.87 reliable index via Spearman-Brown Coefficient Correlation was used for data collection. Data were collected through face-to-face administration and presented in tables. Descriptive and inferential statistics were applied in data analysis using SPSS Version 23 IBM. Chi-square was used to test the hypothesis at 0.95 alpha. Results from the study revealed poor implementation of preventive strategies against malaria among the College students. Students that implement the strategies go by sewage disposal (80.1%), environmental sanitation (71.5%), and keeping windows and doors closed at night (51.3%). The major challenges faced by the students in the implementation of the strategies are: sweating too much while sleeping under ITN (80.1%) and allergic reactions to insecticide sprays (67.3%). The study also revealed that year of study, gender, and course of study are associated with practice of malaria prevention strategies among the college students as students at higher level do not implement the prevention strategies.